Literary exhortations : the early fiction of George A. Birmingham - Dineen, Gerard (Trinity College (Dublin, Ireland). School of English, 2010)
This thesis will demonstrate the important cultural contribution of the early fiction of the Irish writer George A. Birmingham (1865 - 1950). Born in Belfast on the eve of the disestablishment of the Church of Ireland and living through one of the most eventful periods in modern Irish history, this thesis will show that Birmingham's first four novels constitute an important part of the literary map of early twentieth century Ireland.
Keywords: English, Ph.D.; Ph.D. Trinity College Dublin.